The burden of cutaneous disease in solid organ transplant recipients of color. Issue 3 (5th September 2020) - Kentley, Jonathan; Allawh, Rina; Rao, Swati; Doyle, Alden; Ahmad, Amar; Nadhan, Kumar; Proby, Charlotte; Harwood, Catherine A.; Chung, Christina L.
Abstract : Organ transplant recipients (OTRs) are at increased risk of cutaneous malignancy. Skin disorders in OTRs of color (OTRoC) have rarely been systematically assessed. We aimed to ascertain the burden of skin disease encountered in OTRoC by prospectively collecting data from OTRs attending 2 posttransplant skin surveillance clinics: 1 in London, UK and 1 in Philadelphia, USA. Retrospective review of all dermatological diagnoses was performed. Data from 1766 OTRs were analyzed: 1024 (58%) white, 376 (21%) black, 261 (15%) Asian, 57 (3%) Middle Eastern/Mediterranean (ME/M), and 48 (2.7%) Hispanic; and 1128 (64%) male. Viral infections affected 45.1% of OTRs, and were more common in white and ME/M patients ( P < .001). Fungal infections affected 28.1% and were more common in ME/M patients ( P < .001). Inflammatory skin disease affected 24.5%, and was most common in black patients ( P < .001). In addition, 26.4% of patients developed skin cancer. There was an increased risk of skin cancer in white vs nonwhite OTRs (HR 4.4, 95% CI 3.5‐5.7, P < .001): keratinocyte cancers were more common in white OTRs ( P < .001) and Kaposi sarcoma was more common in black OTRs ( P < .001). These data support the need for programs that promote targeted dermatology surveillance for all OTRs, regardless of race/ethnicity or country of origin. Abstract : In a diverse cohort of organ transplant recipients, skin disease is prevalent in all groups, regardless of race, ethnicity, or country of origin.